Students’ Perceptions and Contributing Factors in Learning English in Junior High School - Luthfi Zahra Marsenda; Susiati (Prodi Tadris Bahasa Inggris, 2025)
This study examines the perceptions and factors of junior high school students that affect their interest in learning English in rural schools in the Klaten area. English proficiency is essential for future career prospects and as a global communication, but gaps in resources and teaching methods pose challenges, especially in rural settings. Data were collected from first-graders at a junior high school in Klaten, Indonesia, through a structured questionnaire using a quantitative research design. The study investigated intrinsic factors such as motivation and confidence, as well as external factors such as the quality of teaching, facilities at the school, peer support, and access to resources. The results showed that intrinsic factors such as confidence and focus were very important, but external factors such as the perceived usefulness of English for global communication also significantly influenced student engagement. Statistical analysis highlights the benefits of formative assessment in improving learning outcomes compared to summative evaluation. These findings underscore the need for tailored teaching strategies, resource allocation, and supportive learning environments to bridge gaps and foster positive attitudes towards English language learning. This research offers valuable insights for educators and policymakers to create an inclusive and engaging English education framework that meets the diverse needs of rural students in Indonesia.